2010
DOI: 10.1007/s00216-010-4335-y
|View full text |Cite
|
Sign up to set email alerts
|

Separation of short-chain branched polyolefins by high-temperature gradient adsorption liquid chromatography

Abstract: A new separation principle was recently introduced into the analytical characterization of polyolefins by researchers from the German Institute for Polymers in Darmstadt. It was demonstrated that polyolefins can be selectively separated via high-performance liquid chromatography on the basis of their adsorption/desorption behaviours at temperatures as high as 160 °C. A Hypercarb® column packed with porous graphite gave the best results. The mobile phase consisted of a mixture of 1-decanol and 1,2,4-trichlorobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 53 publications
5
42
1
Order By: Relevance
“…In Figure 3b the data for LCB samples are scattered without indicating a correlation with the average molar mass of the samples. This is in agreement with our findings [27] that SCB has a stronger adsorption effect than the molar mass on the retention behavior of LLDPE samples in the system 1-decanol!TCB.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…In Figure 3b the data for LCB samples are scattered without indicating a correlation with the average molar mass of the samples. This is in agreement with our findings [27] that SCB has a stronger adsorption effect than the molar mass on the retention behavior of LLDPE samples in the system 1-decanol!TCB.…”
Section: Resultssupporting
confidence: 94%
“…[26,27] The long chain branches in the model LCB PE are much longer (M n per arm ¼ 10-24 kg/mol $ 700-1700 carbons, Table 1). If the LCB of the model LCB polyethylenes studied here were unbranched, this effect could probably be seen.…”
Section: Resultsmentioning
confidence: 99%
“…Independence of the elution volumes on the molar mass >15-20 kg/mol was also found for PE [164] and EP, EB, EO and ethylene/1-decene copolymers [161]. It is typical for adsorption phenomena that adsorption depends on the shape of a molecule, on positions and numbers of functional groups, on polarizability of the molecule, as well as on the type and nature of the sorbent and the solvents.…”
Section: Polyolefinsmentioning
confidence: 85%
“…It was found that both comonomers, ethylene and diene, are adsorbed. On the other hand, adsorption of EP [164], ethylene-butene (EB), ethylene-hexene (EH), ethylene-octene (EO) or ethylene/1-decene copolymers depends linearly on the average content of ethylene [161]. This is very practical from the point of evaluation of chromatograms.…”
Section: Polyolefinsmentioning
confidence: 98%
“…Though the combination of solvents used in HT-HPLC may differ, the mechanism of separation when the Hypercarb V R stationary phase is used is commonly agreed. 9,[33][34][35] Copolymer chains interact with the stationary phase via van der Waals forces. The strength of the interactions is based upon the length of the ethylene sequences (nE) in the copolymer chain in contact with the stationary phase.…”
Section: Chemical Composition Separationmentioning
confidence: 99%